Referendum in Moldova: A Hesitating Choice for the European Path - Andrei, Roxana (The Hague Research Institute for Eastern Europe, the South Caucasus & Central Asia, 2024)
Moldova: not as close as expected On 20 October 2024, a large part of the voters in Moldova casted a negative vote against their country joining the European Union (EU), by voting against changing the constitution of their country in order for the Republic of Moldova to join the EU. The referendum, organised at the same time with the first round of the presidential elections, barely passed with 50.35% votes in favour, but only after collecting the votes of the Western diaspora, where Moldovans voted 76.79% for the Yes option (ADEPT, 2024). Regardless the final result of the referendum, the hard truth remains unchanged: the people living in Moldova were not fully convinced by the European way strongly advocated by the president in power, Maia Sandu, a former World Bank economist.